2018
DOI: 10.4049/jimmunol.1800365
|View full text |Cite
|
Sign up to set email alerts
|

Perforin-2 Breaches the Envelope of Phagocytosed Bacteria Allowing Antimicrobial Effectors Access to Intracellular Targets

Abstract: Perforin-2, the product of the MPEG1 gene, limits the spread and dissemination of bacterial pathogens in vivo. It is highly expressed in murine and human phagocytes, and macrophages lacking Perforin-2 are compromised in their ability to kill phagocytosed bacteria. In this study we used Salmonella enterica serovar Typhimurium as a model intracellular pathogen to elucidate the mechanism of Perforin-2’s bactericidal activity. In vitro Perforin-2 was found to facilitate the degradation of antigens contained within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 62 publications
(101 reference statements)
1
30
1
Order By: Relevance
“…Although the precise details are under investigation, perforin-2 is trafficked to endo/phagosomes where it polymerizes into a pre-pore structure that subsequently transitions to a pore conformation upon phagosome acidification (2,4,8). These pores perforate the envelope of phagocytosed pathogens, rendering them more susceptible to antimicrobial effector such as proteases, other hydrolases, and reactive oxygen and nitrogen species (2,5). Studies of Mpeg1 knockout mice have shown that deficiencies in this protein lead to uncontrolled, disseminated infection from the gut and skin, as well as a host of other immunologic consequences (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise details are under investigation, perforin-2 is trafficked to endo/phagosomes where it polymerizes into a pre-pore structure that subsequently transitions to a pore conformation upon phagosome acidification (2,4,8). These pores perforate the envelope of phagocytosed pathogens, rendering them more susceptible to antimicrobial effector such as proteases, other hydrolases, and reactive oxygen and nitrogen species (2,5). Studies of Mpeg1 knockout mice have shown that deficiencies in this protein lead to uncontrolled, disseminated infection from the gut and skin, as well as a host of other immunologic consequences (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…MPEG1 expression is constitutive in phagocytes and inducible in parenchymal cell lines by interferons or bacterial infection (1,2). Its function in innate immunity is vital for intracellular pathogen elimination such that Mpeg1 knockout mice exhibit increased susceptibility to infections (2)(3)(4)(5). MPEG1 variants can confer an immunodeficiency hallmarked by polymicrobial infections (1).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of minute quantities of lysozyme, however, were sufficient to kill pre-treated M. smegmatis, putatively indicating MPEG1 perforates the outer membrane but does not affect the integrity of the peptidoglycan layer (90). Indeed, more recent studies have found MPEG1 facilitates the entry of myriad anti-microbial effectors into cells including; proteases, reactive oxygen and nitrogen species, bactericidal peptides and the harsh acidic environment of the phagosome (93). Notably, recombinant MPEG1 possesses lytic activity which is strictly dependent on low pH (82,83).…”
Section: Mpeg1 Function In Immunitymentioning
confidence: 99%
“…Other bactericidal molecules have been found to be less effective in the absence of P2, suggesting that P2 is essential for the activity of mammalian immune defense mechanisms. It has recently been shown that P2 facilitates the delivery of proteases and other antimicrobial effectors to the sites of bacterial infection leading to effective killing of phagocytosed bacteria (4).…”
Section: Introductionmentioning
confidence: 99%